The Effectiveness Of Story Face In Teaching Reading : (A Pre-Experimental Study At Class Xi Female Of SMA IT Misykat Al-Anwar Kwaron Jombang) - Desi Agustin; Sayid Ma'rifatulloh (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
As an international language, English is widely used in many countries for communication. This widespread use makes English important for many aspects of life including education. Consequently, English is a mandatory subject in schools, studied from elementary levels through to university. It leads to the point of how important the mastery of English for all the students. Furthermore, the ultimategoal of English instruction is emphasized on developing students' communicative competence. This research use pre-experimental design with a quantitative approach to collect data. Quantitative methods involve gathering, analyzing, interpreting, and reporting results. The research utilized an experimental approach to evaluate students' achievement differences after receiving treatment. The Story Face strategy was used to teach students. They were given a pre-test before the treatment and a post-test after to measure any differences in reading comprehension. The specific design used was a one-group pre-test and post-test. The researchers concluded that the Story Face strategy significantly improved reading comprehension among female students in class XI at SMA Misykat Al-Anwar Kwaron Jombang. This conclusion is substantiated by the quantitative data, showing a dramatic increase in reading comprehension scores from the pre-test to the post-test. Specifically, the average score improved from a "Poor" category (33.64) to a "Very Good" category (80.91), highlighting the strategy's effectiveness